In vivo efficacy of artemether–lumefantrine against uncomplicated Plasmodium falciparum malaria in Dembia District, northwest Ethiopia - Deressa T; Seid ME; Birhan W; Aleka Y; Tebeje BM (Dove Medical Press, 2017)
Tekalign Deressa,1 Mengistu Endris Seid,1 Wubet Birhan,1 Yetemwork Aleka,1 Biniam Mathewos Tebeje1,2 1School of Biomedical and Laboratory Sciences, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Molecular Parasitology Laboratory, Queensland Institute of Medical Research, Brisbane, Australia Background: Artemether–lumefantrine (AL) has been used as a first-line treatment for uncomplicated Plasmodium falciparum malaria in Ethiopia since 2004. Antimalarial drug resistance is one of the major obstacles for malaria control and curtails the lifespan of several drugs. Thus, continued monitoring of the efficacy of AL is of great public health importance in malaria endemic areas. Objective: This study aimed to investigate the therapeutic efficacy and safety of AL for the treatment of uncomplicated P. falciparum malaria in the Dembia district, northwest Ethiopia. Methods: A prospective study was conducted from April 2015 to February 2016 at Kola Diba Health Center (KHC) in the Dembia district to determine the therapeutic efficacy and safety of AL for the treatment of uncomplicated P. falciparum monoinfection. Patients were treated with the six-dose regimen of AL over 3 days and followed up for 28 days as per the World Health Organization protocol. Results: Of the total 80 patients enrolled in the AL efficacy study, 75 patients completed the 28 days follow-up. None of the participants reported major adverse events. No early treatment failure or late clinical failure were observed during the study, but there were 6 (8.0%) late parasitological failures. The uncorrected per protocol cure rate of AL was 92.0 (95% CI: 85.7–98.3). Treatment with AL cleared parasitemia and fever in >95% of the patients by day 3. Conclusion: This study showed that AL is well tolerated and remains efficacious for treatment of uncomplicated P. falciparum malaria in northwest Ethiopia. However, the observed late parasitological failures in this study are of a concern and warrant continued monitoring of drug efficacy as per the World Health Organization recommendations. Keywords: artemether–lumefantrine, uncomplicated Plasmodium falciparum, Ethiopia, malaria, antimalarial efficacy